Laminate, packaging material

The gas barrier laminate, featuring a barrier layer and aqueous non-halogen-containing resin, addresses the recyclability issues of traditional packaging materials by enabling easy separation and recycling while maintaining gas barrier properties.

JP2025040597APending Publication Date: 2025-03-25DIC CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023147500
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing packaging materials, particularly laminates used for food and daily necessities, are difficult to recycle due to the challenge of separating different types of resin films.

Method used

A gas barrier laminate is developed, comprising a first substrate, a second substrate with heat sealing properties, and a gas barrier adhesive layer in between. At least one of the substrates includes an aqueous non-halogen-containing resin, and a barrier layer with a film thickness of 0.1 μm to 1 μm is incorporated to enhance recyclability.

Benefits of technology

The laminate provides excellent recyclability and maintains effective gas barrier properties, making it suitable for packaging materials that can be easily recycled while maintaining product integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025040597000001
    Figure 2025040597000001
  • Figure 2025040597000002
    Figure 2025040597000002
Patent Text Reader

Abstract

To provide a gas barrier laminate with excellent recyclability and a packaging material using the laminate.SOLUTION: The laminate includes a first substrate, a second substrate containing the same type of resin as the first substrate and having heat sealability, and a gas barrier adhesive layer arranged between the first substrate and the second substrate, wherein at least one of the first substrate and the second substrate contains a water-based non-halogen-containing resin, and includes a barrier layer with a film thickness of 0.1 μm or more and 1 μm or less. The packaging material is obtained using the laminate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a gas barrier laminate having excellent recyclability, and a packaging material obtained by using the gas barrier laminate. [Background technology]

[0002] Packaging materials used for packaging food and daily necessities are usually made of a laminate in which a heat-sealable film such as a polyethylene film or a polypropylene film is bonded to a resin film having excellent heat resistance and strength such as a polyester film or a nylon film using an adhesive (Patent Documents 1 and 2). Two-component polyurethane adhesives made of polyol and isocyanate are known as adhesives used for such laminates.

[0003] Meanwhile, in recent years, along with the growing demand for the creation of a recycling-oriented society, attempts have been made to recycle and reuse packaging materials. However, in the case of laminates in which different types of resin films are laminated together as described above, it is difficult to separate the resins by type, and therefore the laminates are not suitable for recycling. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2014-004799 A [Patent Document 2] JP 2004-238050 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in view of the above background, and an object of the present invention is to provide a gas barrier laminate having excellent recyclability, and a packaging material using said laminate. [Means for solving the problem]

[0006] The present invention relates to a laminate comprising a first substrate, a second substrate containing the same resin type as the first substrate and having heat sealability, and a gas barrier adhesive layer disposed between the first substrate and the second substrate, wherein at least one of the first substrate and the second substrate comprises a barrier layer containing an aqueous non-halogen-containing resin and having a thickness of 0.1 μm or more and 1 μm or less. Effect of the Invention

[0007] According to the laminate of the present invention, a gas barrier laminate and a packaging material having excellent recyclability can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] <Laminate> The laminate of the present invention includes a first substrate, a second substrate, a barrier layer, and a gas barrier adhesive layer. The laminate of the present invention will be described in detail below.

[0009] (First substrate) The first substrate can be any film or sheet (unless otherwise specified below, film is a general term for film and sheet) that has excellent chemical and physical strength, and can be used without any particular restrictions. The substrate may be a single-layer film or a multi-layer laminate film. It can be appropriately selected depending on the use conditions, such as the contents and type of the packaging material described below, and whether or not heat treatment is performed after filling the contents.

[0010] Specific examples of the first substrate include low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, polypropylene, polybutene, polyvinyl alcohol, ethylene-vinyl acetate copolymer, ionomer, ethylene-(meth)acrylic acid copolymer, ethylene-(meth)acrylic acid ester copolymer, ethylene-propylene copolymer, methylpentene, polyacrylonitrile, acrylonitrile-styrene copolymer, acrylonitrile-butadiene-styrene copolymer, polycarbonate, polyvinyl chloride (PVC), polyvinylidene chloride (PVDC), polyvinylidene fluoride (PVDF), ethylene-tetrafluoroethylene copolymer (ETFE), polytetrafluoroethylene (PTFE), polyethylene terephthalate (PET), polybutylene terephthalate, polyethylene naphthalate, and other resin films, K-coated stretched polypropylene film, K-coated stretched nylon film, and composite films formed by laminating two or more of these films, but are not limited thereto.

[0011] It is also preferable to use a film formed from a material containing a biomass-derived component. Biomass films are commercially available from various companies, and for example, sheets such as those listed in the list of biomass certified products listed in the Japan Organics Resources Association can be used.

[0012] Specifically, a well-known film is made from biomass-derived ethylene glycol. Biomass-derived ethylene glycol is made from ethanol (biomass ethanol) produced from biomass. For example, biomass-derived ethylene glycol can be obtained by a method of producing ethylene glycol from biomass ethanol via ethylene oxide using a conventionally known method. Commercially available biomass ethylene glycol may also be used, and for example, biomass ethylene glycol commercially available from India Glycoal Limited can be suitably used.

[0013] Alternatively, products using biomass raw materials classified by the degree of biomass plastic as stipulated by ISO16620 or ASTM D6866 are also on the market. Radioactive carbon-14C exists in the atmosphere at a ratio of 1 in 1012 particles, and this ratio does not change even with atmospheric carbon dioxide, so this ratio does not change even in plants that fix this carbon dioxide through photosynthesis. For this reason, the carbon in plant-derived resins contains radioactive carbon-14C. In contrast, the carbon in fossil fuel-derived resins contains almost no radioactive carbon-14C. Therefore, by measuring the concentration of radioactive carbon-14C in the resin with an accelerator mass spectrometer, the proportion of plant-derived resin in the resin, i.e., the degree of biomass plastic, can be determined. Examples of plant-derived low-density polyethylene, which is a biomass plastic having a biomass plastic content of 80% or more, preferably 90% or more as specified by ISO16620 or ASTM D6866, include Braskem products under the trade names "SBC818", "SPB608", "SBF0323HC", "STN7006", "SEB853", and "SPB681", and films using these as raw materials can be preferably used.

[0014] The thickness of the first base material is not particularly limited, and may be appropriately selected in the range of 1 to 300 μm from the viewpoint of moldability and transparency. It is preferably in the range of 1 to 100 μm. If it is less than 1 μm, the strength is insufficient, and if it exceeds 300 μm, the rigidity is too high, which may make processing difficult.

[0015] The first substrate may be one that has been subjected to some kind of surface treatment, for example, a physical treatment such as a corona discharge treatment, an ozone treatment, a low-temperature plasma treatment using oxygen gas or nitrogen gas, or a glow discharge treatment, a chemical treatment such as an oxidation treatment using a chemical agent, or other treatment.

[0016] The first substrate can be produced by a conventionally known film-forming method such as an extrusion method, a cast molding method, a T-die method, a cutting method, or an inflation method using one or more resins selected from the above-mentioned resins. Alternatively, the first substrate can be produced by a multilayer co-extrusion film-forming method using two or more resins selected from the above-mentioned resins. From the viewpoint of strength, dimensional stability, and heat resistance of the film, the film may be stretched in a uniaxial or biaxial direction using a tenter method, a tubular method, or the like.

[0017] The first base material may contain additives as necessary. Specifically, plastic compounding agents and additives such as lubricants, crosslinking agents, antioxidants, ultraviolet absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, and pigments may be added for the purpose of improving or modifying processability, heat resistance, weather resistance, mechanical properties, dimensional stability, antioxidant properties, slipperiness, mold releasability, flame retardancy, antifungal properties, electrical properties, strength, etc. The amount of additives added is adjusted within a range that does not affect other properties.

[0018] (Second substrate) The second substrate includes a film and has a heat sealability that allows the two substrates to melt and fuse together when heated. The film may be the same as that of the first substrate.

[0019] The film may be a stretched film stretched uniaxially or biaxially, or may be an unstretched film. When stretched biaxially, for example, the film is longitudinally stretched 2 to 4 times by a roll stretching machine at 50 to 100°C, and then transversely stretched 3 to 5 times by a tenter stretching machine in an atmosphere of 90 to 150°C, and then heat-treated in an atmosphere of 100 to 240°C by the same tenter to obtain the film. The stretched film may be simultaneously biaxially stretched or sequentially biaxially stretched.

[0020] The thickness of the second base material can be selected arbitrarily, but from the viewpoint of strength as a packaging material, it is preferably 5 to 500 μm, and more preferably 10 to 250 μm.

[0021] The second substrate may be only a film if the film itself has heat-sealing properties, or may be a film coated with a heat-sealing agent containing a heat-sealable resin and a solvent, and the solvent is dried to form a heat-sealing layer.

[0022] Examples of the heat-sealable resin include thermoplastic resins such as shellacs, rosins, rosin-modified maleic acid resins, rosin-modified phenolic resins, nitrocellulose, cellulose acetate, cellulose acetyl propionate, cellulose acetyl butyrate, chlorinated rubber, cyclized rubber, vinyl chloride, vinylidene chloride, polyamide resins, vinyl chloride-vinyl acetate copolymers, polyester resins, ketone resins, butyral resins, chlorinated polypropylene resins, chlorinated polyethylene resins, chlorinated ethylene vinyl acetate resins, ethylene vinyl acetate resins, acrylic resins, urethane resins, ethylene-vinyl alcohol resins, styrene-maleic acid resins, casein, and alkyd resins, which may be used alone or in combination of two or more. From the viewpoint of recyclability, it is preferable to use the same resin type as the film, but since it is easily recyclable as long as 90% of the total thickness of the laminate of the present invention is the same resin type, the heat-sealable resin used in the heat-sealing agent may be different from the film.

[0023] The heat sealing agent may be in any form, such as a type in which these resins are dissolved in an organic solvent, a type in which these resins are dissolved in water or an aqueous organic solvent, or an emulsion type in which an acrylic emulsion, a urethane emulsion, a polyvinyl alcohol resin, an ethylene-vinyl alcohol emulsion, an ethylene-methacrylic acid emulsion, a polyolefin emulsion, an ethylene vinyl acetate emulsion, or the like is dispersed in water or an aqueous organic solvent.

[0024] The organic solvent is not particularly limited, and examples thereof include various organic solvents such as aromatic hydrocarbons, such as toluene, xylene, Solvesso #100, and Solvesso #150; aliphatic hydrocarbons, such as hexane, heptane, octane, and decane; and esters, such as methyl acetate, ethyl acetate, isopropyl acetate, butyl acetate, amyl acetate, ethyl formate, and butyl propionate.

[0025] Examples of aqueous organic solvents include alcohols such as methanol, ethanol, propanol, and butanol; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; and glycol ethers such as ethylene glycol (mono, di)methyl ether, ethylene glycol (mono, di)ethyl ether, ethylene glycol monopropyl ether, ethylene glycol monoisopropyl ether, monobutyl ether, diethylene glycol (mono, di)methyl ether, diethylene glycol (mono, di)ethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol monobutyl ether, triethylene glycol (mono, di)methyl ether, propylene glycol (mono, di)methyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, and dipropylene glycol (mono, di)methyl ether.

[0026] The heat-sealing agent may contain components other than the heat-sealable resin and the solvent, such as wax, filler, defoamer, viscosity modifier, leveling agent, tackifier, preservative, antibacterial agent, rust inhibitor, antioxidant, etc.

[0027] The heat sealing agent can be applied by a known method, such as a roll coater, gravure coater, flexo coater, air doctor coater, blade coater, air knife coater, squeeze coater, impregnation coater, transfer roll coater, kiss coater, curtain coater, cast coater, spray coater, die coater, offset printing machine, screen printing machine, etc. After application, a drying step may be performed in an oven, etc.

[0028] The thickness of the heat seal layer (the amount of heat sealant applied (solid content)) may be any value. For example, the thickness is 0.5 g / m 2 ~5g / m 2 It is.

[0029] The second substrate contains the same resin type as the first substrate. This allows a laminate with excellent recyclability. Both the first substrate and the second substrate preferably contain a polyester resin or an olefin resin, and more preferably contain an olefin resin. When both the first substrate and the second substrate contain a polyester resin, the first substrate is, for example, a PET film, and the second substrate is a PET film having heat sealability. When both the first substrate and the second substrate contain an olefin resin, the first substrate is, for example, selected from a biaxially oriented polypropylene film (OPP), a biaxially oriented polyethylene film (OPE), a uniaxially oriented polyethylene film (MDOPE), and a high density polyethylene film (HDPE), and the second substrate is selected from an unoriented polypropylene film (CPP) and a low density polyethylene film (LLDPE).

[0030] (Barrier layer) At least one of the first substrate and the second substrate includes a barrier layer. The barrier layer is a layer containing an aqueous (water-soluble or water-swellable) non-halogen-containing resin that has excellent oxygen barrier properties under low humidity conditions (for example, humidity of 50% or less). Examples of such resins include polyvinyl alcohol, ethylene-vinyl alcohol copolymers, polycarboxylic acids, polyalkyleneimines, etc. The thickness of the barrier layer is 0.1 μm or more and 1 μm or less.

[0031] Ethylene-vinyl alcohol copolymers can be obtained by hydrolysis of copolymers of ethylene and vinyl esters. Examples of vinyl esters include vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl versatate, vinyl caproate, vinyl caprylate, vinyl laurate, vinyl palmitate, vinyl stearate, vinyl oleate, and vinyl benzoate, and one or more of these can be used in combination. It is preferable to use vinyl acetate.

[0032] The content of ethylene units in the ethylene-vinyl alcohol copolymer is preferably 20 mol% or more and 60 mol% or less. If it is less than 20 mol%, the bending resistance, viscosity stability, and thermal stability during melt molding tend to decrease. If it exceeds 60 mol%, the gas barrier property tends to decrease. Components other than ethylene and vinyl ester, such as propene, 1-butene, isobutylene, 1,3-butadiene, isopropenyl acetate, 2-propenyl acetate, styrene, α-methylstyrene, vinyl chloride, acrylonitrile, maleic anhydride, methyl acrylate, methyl methacrylate, N-vinyl-N-methylformamide, vinylacetamide, N-vinylformamide, N-(hydroxymethyl)-N-vinylformamide hydroxyethyl acrylate, methyl vinyl ketone, and diacetone acrylamide may be copolymerized, but it is preferable to keep these components at 30 mol% or less.

[0033] The saponification degree of the ethylene-vinyl alcohol copolymer is preferably 90 mol% or more, more preferably 95 mol% or more, because it has excellent gas barrier properties, viscosity stability, thermal stability during melt molding, moisture resistance, etc. It may be completely saponified. The saponification degree can be measured by FTIR using, for example, a Nicolet 5700 FTIR spectrometer controlled by OMNIC software.

[0034] The ethylene-vinyl alcohol copolymer preferably has a melting point of less than 180°C and more preferably 130°C or higher. The glass transition temperature is preferably 45°C or higher and 65°C or lower.

[0035] Polyvinyl alcohol can be obtained by hydrolyzing the vinyl ester copolymer as described above. The degree of saponification is preferably 90 mol% or higher, more preferably 95 mol% or higher. It may be completely saponified. The melting point of polyvinyl alcohol is preferably 200°C or higher. Also, the glass transition temperature of polyvinyl alcohol is preferably 65°C or higher and 85°C or lower.

[0036] The glass transition temperature and melting point of the ethylene-vinyl alcohol copolymer and polyvinyl alcohol are measured as follows. Using a differential scanning calorimeter (DSC-7000 manufactured by SII NanoTechnology Inc., hereinafter referred to as DSC), 5 mg of the sample is heated from 30°C at a rate of 10°C / min to T1°C under a nitrogen stream of 20 mL / min and then held for 10 minutes. Then, it is cooled to T2°C at a rate of 10°C / min to remove the thermal history. After holding at T2°C for 5 minutes, it is heated again to T3°C at a rate of 10°C / min to measure the DSC curve. The intersection of the straight line obtained by extending the baseline on the low-temperature side in the measurement results observed in the second heating process to the high-temperature side and the tangent line drawn at the point where the slope of the curve of the stepped portion of the glass transition is maximized is defined as the glass transition point, and the temperature at this time is defined as the glass transition temperature. Also, the maximum peak temperature of the endothermic curve observed in the second heating process is defined as the melting point.

[0037] T2 < T3 ≤ T1, T2 is sufficiently lower than the glass transition temperature of the sample, and T1 and T3 are temperatures at least 30°C or higher than the melting point of the sample. As an example, T1 is 200°C, T2 is -80°C, and T3 is 200°C, but it is appropriately adjusted according to the sample to be measured.

[0038] The polyalkyleneimine is a resin having a polyalkyleneimine skeleton, and is obtained by polymerizing one or more alkyleneimines (e.g., ethyleneimine, propyleneimine) by a conventional method. The polyalkyleneimine may be a linear polyalkyleneimine having a linear polyalkyleneimine chain, or a branched polyalkyleneimine having a branched polyalkyleneimine chain.

[0039] Examples of polyalkyleneimines include polyethyleneimine and polypropyleneimine. The polyalkyleneimine may have a substituent (e.g., hydroxypropyl group, hydroxyethyl group) introduced into at least a part of the nitrogen atoms of the polyalkyleneimine chain. The polyalkyleneimine may be modified with an organometallic compound such as tetraisopropyl titanate, tetranormalbutyl titanate, butyl titanate dimer, tetra(2-ethylhexyl) titanate, tetramethyl titanate, polyhydroxytitanium stearate, titanium bisacetylacetonate, titanium tetraacetylacetonate, polytitanium acetylacetonate, titanium octylene glycolate, titanium ethylacetoacetate, titanium lactate, titanium triethanolamine, or titanium stearate, or two or more polyalkyleneimines may be used in combination.

[0040] When the polyalkyleneimine is branched, the degree of branching can be expressed by the ratio of primary, secondary and tertiary amino groups contained in the polyalkyleneimine. As an example, it is preferable to use a polyalkyleneimine having a ratio of primary amino groups of 20 to 40%, a ratio of secondary amino groups of 30 to 60% and a ratio of tertiary amino groups of 20 to 35%. The ratios of primary, secondary and tertiary amine groups contained in the polyalkyleneimine are as follows: 13 It can be measured by C-NMR spectroscopy. The branched polyalkyleneimine is preferably a branched polyethyleneimine.

[0041] The number average molecular weight of the polyalkyleneimine can be appropriately adjusted, and is, for example, from 5,000 to 100,000. The number average molecular weight of the polyalkyleneimine can be measured by GPC (gel permeation chromatography) using pullulan as a standard substance.

[0042] The polycarboxylic acid is at least one selected from homopolymers, copolymers, and salts thereof of unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, etc. Examples of the polycarboxylate include alkali metal salts, quaternary ammonium salts, and alkanolamine salts of polycarboxylate. The polycarboxylic acid preferably has a weight average molecular weight of about 1,000 to 50,000.

[0043] In one embodiment of the present invention, the barrier layer is provided on the surface of the first substrate and / or the second substrate by lamination, coextrusion, spraying, deposition, or coating. In one embodiment of the present invention, the barrier layer is provided in the first substrate and / or the second substrate by coextrusion.

[0044] When the barrier layer is provided by coating, the above-mentioned resin is dissolved or dispersed in a solvent to prepare a coating agent, which is then applied. As the solvent, water, water-soluble organic solvents that dissolve in water, etc. can be used. As the water, pure water such as ion-exchanged water, ultrafiltered water, reverse osmosis water, distilled water, etc., or ultrapure water can be used. From the viewpoint of long-term storage, it is preferable to use water that has been sterilized by ultraviolet irradiation or addition of hydrogen peroxide, etc., in order to prevent the growth of mold or bacteria.

[0045] Examples of water-soluble organic solvents include glycols such as ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, propylene glycol, polyethylene glycol, and polypropylene glycol; diols such as butanediol, pentanediol, and hexanediol; glycol esters such as propylene glycol laurate; diethylene glycol ethers such as diethylene glycol monoethyl, diethylene glycol monobutyl, diethylene glycol monohexyl, and carbitol; glycol ethers such as propylene glycol ether, dipropylene glycol ether, and cellosolve including triethylene glycol ether; alcohols such as methanol, ethanol, isopropyl alcohol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, butyl alcohol, and pentyl alcohol; lactones such as sulfolane, esters, ketones, and γ-butyrolactone, lactams such as N-(2-hydroxyethyl)pyrrolidone, and various other solvents known as aqueous organic solvents, such as glycerin and its polyalkylene oxide adducts, can be mentioned. These aqueous organic solvents can be used alone or in combination of two or more.

[0046] When providing a barrier layer in the substrate, for example, substrate material such as polyethylene is supplied to two of three extruders, and barrier layer material such as ethylene-vinyl alcohol copolymer is supplied to the remaining one, and they are co-extruded to obtain a film in which a barrier layer is provided in the substrate, such as polyethylene / ethylene-vinyl alcohol copolymer / polyethylene.

[0047] The barrier layer preferably contains an inorganic compound, which allows the laminate to have better gas barrier properties. Examples of inorganic compounds include hydrated silicates (phyllosilicate minerals, etc.), kaolinite-serpentine clay minerals (halloysite, kaolinite, endelite, dickite, nacrite, etc., antigorite, chrysotile, etc.), pyrophyllite-talc (pyrophyllite, talc, keroli, etc.), smectite clay minerals (montmorillonite, beidellite, nontronite, saponite, hectorite, sauconite, stevensite, etc.), vermiculite clay minerals (vermiculite, etc.), mica or mica clay minerals (muscovite, phlogopite, etc., mica, margarite, tetrasilylic mica, taeniolite, etc.), chlorite (cookite, sudoite, clinochlore, chamosite, nimite, etc.), hydrotalcite, plate-like barium sulfate, boehmite, aluminum polyphosphate, etc. These minerals may be natural clay minerals or synthetic clay minerals. The inorganic compounds can be used alone or in combination of two or more.

[0048] The inorganic compound may be particulate or plate-like. In this specification, the particulate shape of the inorganic compound refers to an aspect ratio of 1 to 1.5, and the plate-like shape refers to an aspect ratio of more than 1.5. The upper limit of the aspect ratio of the plate-like inorganic compound is not particularly limited, but is preferably 100 or less from the viewpoint of coatability.

[0049] The average particle size of the inorganic compound is not particularly limited, but when the inorganic compound is particulate, it is preferably 10 nm or more, for example. The upper limit of the average particle size is adjusted as appropriate, but is, for example, 1 μm or less. In this specification, the average particle size of the inorganic compound refers to the particle size that appears most frequently when the particle size distribution of the inorganic compound is measured using a light scattering measuring device. When the inorganic compound has a plate-like shape, the thickness is preferably, for example, 0.05 μm to 0.1 μm and the length is preferably 0.1 μm to 10 μm. The thickness and length of the inorganic compound are measured by the same method as for the particle size distribution.

[0050] When both the first substrate and the second substrate have a barrier layer, both the first substrate and the second substrate may have a barrier layer on the substrate surface, or both the first substrate and the second substrate may have a barrier layer in the substrate. The first substrate may have a barrier layer on the substrate surface and the second substrate may have a barrier layer in the substrate, or the first substrate may have a barrier layer in the substrate and the second substrate may have a barrier layer on the substrate surface. When the barrier layer is provided on the surface of the first substrate, the barrier layer is preferably disposed so as to be located between the first substrate and the gas barrier adhesive layer described below. When the barrier layer is provided on the surface of the second substrate, the barrier layer is preferably disposed so as to be located between the second substrate and the gas barrier adhesive layer described below.

[0051] (Gas barrier adhesive layer) The gas barrier adhesive layer is a cured coating film of a gas barrier adhesive. The gas barrier adhesive layer is disposed between a first substrate and a second substrate, and these substrates are bonded together directly or via another layer. In this specification, the gas barrier adhesive refers to a gas barrier adhesive having a viscosity of 3 g / m 2 The oxygen barrier property of the coating film applied at 23℃ 0% RH is 300cc / m 2 / day / atm or less, or water vapor barrier of 120g / m 2 / day or less. An example of a gas barrier adhesive preferably used in the present invention is a two-component adhesive comprising a polyol composition (X) containing at least one polyester polyol (A) of the following (A1) to (A3), and a polyisocyanate composition (Y) containing a compound having at least two isocyanate groups in one molecule (hereinafter also simply referred to as an isocyanate compound (B)).

[0052] (1) Polyester polyol (A1) obtained by polycondensation of a polycarboxylic acid including an ortho-oriented polycarboxylic acid and a polyhydric alcohol (2) Polyester polyol having an isocyanuric ring (A2) (3) Polyester polyol having polymerizable carbon-carbon double bonds (A3)

[0053] Examples of ortho-oriented polyvalent carboxylic acids used in the synthesis of polyester polyol (A1) include orthophthalic acid or its anhydride, naphthalene 2,3-dicarboxylic acid or its anhydride, naphthalene 1,2-dicarboxylic acid or its anhydride, anthraquinone 2,3-dicarboxylic acid or its anhydride, and 2,3-anthracene carboxylic acid or its anhydride. These compounds may have a substituent on any carbon atom of the aromatic ring. Examples of the substituent include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimide group, a carboxyl group, a carbamoyl group, an N-ethylcarbamoyl group, a phenyl group, or a naphthyl group.

[0054] The polybasic carboxylic acid used in the synthesis of the polyester polyol (A1) may contain a polybasic carboxylic acid other than the ortho-oriented polybasic carboxylic acid. Examples of polycarboxylic acids other than the ortho-oriented polycarboxylic acid include aliphatic polycarboxylic acids such as succinic acid, adipic acid, azelaic acid, sebacic acid, and dodecanedicarboxylic acid; unsaturated bond-containing polycarboxylic acids such as maleic anhydride, maleic acid, and fumaric acid; alicyclic polycarboxylic acids such as 1,3-cyclopentanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid; terephthalic acid, isophthalic acid, pyromellitic acid, trimellitic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyldicarboxylic acid, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid, and anhydrides or ester-forming derivatives of these dicarboxylic acids; aromatic polycarboxylic acids such as p-hydroxybenzoic acid, p-(2-hydroxyethoxy)benzoic acid, and ester-forming derivatives of these dihydroxycarboxylic acids; and the like. One or more of these may be used in combination. Among these, succinic acid, 1,3-cyclopentanedicarboxylic acid, isophthalic acid and acid anhydrides thereof are preferred.

[0055] When the polycarboxylic acid contains a polycarboxylic acid other than an ortho-oriented polycarboxylic acid, the proportion of the ortho-oriented polycarboxylic acid in the total amount of the polycarboxylic acid is preferably 40 to 100 mass %.

[0056] The polyhydric alcohol used in the synthesis of the polyester polyol (A1) preferably contains at least one selected from the group consisting of ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, and cyclohexanedimethanol, and more preferably contains ethylene glycol.

[0057] The polyhydric alcohol may be used in combination with a polyhydric alcohol other than those mentioned above. Examples of the polyhydric alcohol include aliphatic diols such as 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, dimethylbutanediol, butylethylpropanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, and tripropylene glycol; trihydric or higher polyhydric alcohols such as glycerin, trimethylolpropane, trimethylolethane, tris(2-hydroxyethyl)isocyanurate, 1,2,4-butanetriol, pentaerythritol, and dipentaerythritol; hydroquinone, resorcinol, catechol, naphthalenediol, biphenol, bisphenol A, bisphenol F, and tetramethylbiphenol; ethylene oxide-extended products of these; and aromatic polyhydric phenols such as hydrogenated alicyclic alcohols.

[0058] When the polyester polyol (A1) has three or more hydroxyl groups (for convenience, referred to as polyester polyol (a1)), some of the hydroxyl groups may be modified with an acid group. Such a polyester polyol is also referred to as polyester polyol (A1') below. The polyester polyol (A1') is obtained by reacting the polyester polyol (a1) with a polycarboxylic acid or its acid anhydride. The ratio of the hydroxyl groups modified with the polycarboxylic acid is preferably 1 / 3 or less of the hydroxyl groups of the polyester polyol (a1). Examples of the polycarboxylic acid used for modification include, but are not limited to, succinic anhydride, maleic acid, maleic anhydride, fumaric acid, 1,2-cyclohexane dicarboxylic anhydride, 4-cyclohexene-1,2-dicarboxylic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, phthalic anhydride, 2,3-naphthalenedicarboxylic anhydride, trimellitic anhydride, oleic acid, and sorbic acid.

[0059] The polyester polyol (A2) is obtained, for example, by reacting a triol having an isocyanuric ring with a polycarboxylic acid including an ortho-oriented aromatic polycarboxylic acid and a polyhydric alcohol. Examples of the triol having an isocyanuric ring include alkylene oxide adducts of isocyanuric acid such as 1,3,5-tris(2-hydroxyethyl)isocyanuric acid and 1,3,5-tris(2-hydroxypropyl)isocyanuric acid. The ortho-oriented aromatic polycarboxylic acid, polycarboxylic acid, and polyhydric alcohol can be the same as those used for the polyester polyol (A1).

[0060] As the triol compound having an isocyanuric ring, it is preferable to use 1,3,5-tris(2-hydroxyethyl)isocyanuric acid or 1,3,5-tris(2-hydroxypropyl)isocyanuric acid. As the ortho-oriented aromatic polycarboxylic acid, it is preferable to use orthophthalic anhydride. As the polyhydric alcohol, it is preferable to use ethylene glycol.

[0061] The polyester polyol (A3) can be obtained by using a polyvalent carboxylic acid or a polyhydric alcohol having a polymerizable carbon-carbon double bond.

[0062] Examples of polyvalent carboxylic acids having a polymerizable carbon-carbon double bond include maleic anhydride, maleic acid, fumaric acid, 4-cyclohexene-1,2-dicarboxylic acid and its anhydride, 3-methyl-4-cyclohexene-1,2-dicarboxylic acid and its anhydride, etc. It is presumed that the molecular chain is less flexible and less permeable to oxygen as the number of carbon atoms decreases, so maleic anhydride, maleic acid, and fumaric acid are preferred. An example of a polyhydric alcohol having a polymerizable carbon-carbon double bond is 2-butene-1,4-diol.

[0063] In addition to the above, polyvalent carboxylic acids and polyhydric alcohols not having a polymerizable carbon-carbon double bond may be used in combination. As such polyvalent carboxylic acids and polyhydric alcohols, the same ones as those of the polyester polyols (A1) and (A2) can be used. As the polyvalent carboxylic acid, it is preferable to use at least one selected from the group consisting of succinic acid, 1,3-cyclopentanedicarboxylic acid, orthophthalic acid, orthophthalic acid anhydride, and isophthalic acid, and it is more preferable to use at least one orthophthalic acid and its acid anhydride. As the polyhydric alcohol, it is preferable to use at least one selected from the group consisting of ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, and cyclohexanedimethanol, and it is more preferable to use ethylene glycol.

[0064] The hydroxyl value of the polyester polyol (A) is preferably 20 mgKOH / g or more and 250 mgKOH / g or less. If the hydroxyl value is less than 20 mgKOH / g, the molecular weight is too large, so the viscosity of the polyol composition (A) becomes high, and it is necessary to increase the coating temperature when it is used as a solventless adhesive, for example. If the hydroxyl value is more than 250 mgKOH / g, the crosslink density of the cured coating film becomes too high, and the adhesive strength may decrease.

[0065] When the polyester polyol (A) has an acid group, the acid value is preferably 200 mgKOH / g or less. When the acid value exceeds 200 mgKOH / g, the reaction between the polyol composition (X) and the polyisocyanate composition (Y) may be too fast, resulting in a risk of reduced applicability. The lower limit of the acid value is not particularly limited, but is, for example, 20 mgKOH / g or more. When the acid value is 20 mgKOH / g or more, good gas barrier properties and initial cohesion can be obtained due to intermolecular interactions. The hydroxyl value of the polyester polyol (A) can be measured by the hydroxyl value measurement method described in JIS-K0070, and the acid value can be measured by the acid value measurement method described in JIS-K0070.

[0066] The number average molecular weight of the polyester polyol (A) is particularly preferably 300 to 5000, since a crosslinking density that provides an excellent balance between adhesiveness and gas barrier properties can be obtained. The number average molecular weight is more preferably 350 to 3000. The number average molecular weight is calculated from the obtained hydroxyl value and the number of functional groups of the designed hydroxyl group.

[0067] The glass transition temperature of the polyester polyol (A) is preferably from -30°C to 80°C, more preferably from 0°C to 60°C, and even more preferably from 25°C to 60°C, in view of the balance between adhesion to a substrate and gas barrier properties.

[0068] The polyester polyol (A) may be a polyester polyurethane polyol obtained by reacting the polyester polyols (A1) to (A3) with a diisocyanate compound to undergo urethane elongation to give a number average molecular weight of 1000 to 15000. The urethane-elongated polyester polyol contains a molecular weight component and urethane bonds of a certain level or higher, and therefore has excellent gas barrier properties, excellent initial cohesive strength, and is excellent as an adhesive for lamination.

[0069] The polyisocyanate composition (Y), which is one component of the two-component adhesive having gas barrier properties, contains an isocyanate compound (B). The isocyanate compound (B) may be any of the conventionally known compounds without any particular limitation. Examples of the isocyanate compound (B) include tetramethylene diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, or trimers of these isocyanate compounds, and adducts obtained by reacting an excess amount of these isocyanate compounds with low molecular weight active hydrogen compounds such as ethylene glycol, propylene glycol, metaxylylene alcohol, 1,3-bishydroxyethylbenzene, 1,4-bishydroxyethylbenzene, trimethylolpropane, glycerol, pentaerythritol, erythritol, sorbitol, ethylenediamine, monoethanolamine, diethanolamine, triethanolamine, and metaxylylenediamine, and alkylene oxide adducts thereof, various polyester resins, polyether polyols, and polymeric active hydrogen compounds such as polyamides. Polyester polyisocyanates obtained by reacting polyester polyols (A1) to (A3) with a diisocyanate compound in an isocyanate excess ratio between hydroxyl groups and isocyanate groups may be used. These may be used alone or in combination of two or more.

[0070] Also, blocked isocyanate may be used as the isocyanate compound. Examples of the isocyanate blocking agent include phenols such as phenol, thiophenol, methylthiophenol, ethylthiophenol, cresol, xylenol, resorcinol, nitrophenol, and chlorophenol, oximes such as acetoxime, methylethylketoxime, and cyclohexanoneoxime, alcohols such as methanol, ethanol, propanol, and butanol, halogen-substituted alcohols such as ethylene chlorohydrin and 1,3-dichloro-2-propanol, tertiary alcohols such as t-butanol and t-pentanol, lactams such as ε-caprolactam, δ-valerolactam, γ-butyrolactam, and β-propylolactam, and also include aromatic amines, imides, active methylene compounds such as acetylacetone, acetoacetate, and malonic acid ethyl ester, mercaptans, imines, ureas, diaryl compounds, and sodium bisulfite. The blocked isocyanate can be obtained by subjecting the above-mentioned isocyanate compound to an addition reaction with an isocyanate blocking agent by a known, conventional, appropriate method.

[0071] Among these, it is more preferable to use an isocyanate compound having a skeleton derived from xylylene diisocyanate, hydrogenated xylylene diisocyanate, toluene diisocyanate, or diphenylmethane diisocyanate, since good gas barrier properties can be obtained.

[0072] Examples of such isocyanate compounds include a trimer of diisocyanate, a biuret compound synthesized by reaction with an amine, and an adduct compound formed by reaction with an alcohol. Compared with trimers and biuret compounds, adduct compounds have good solubility in organic solvents used in solvent-based adhesives, so that it is preferable to use an adduct compound when the adhesive is solvent-based. As the adduct compound, an adduct compound formed by reaction with an alcohol appropriately selected from the above low molecular weight active hydrogen compounds can be used, and among them, adduct compounds with an ethylene oxide adduct of trimethylolpropane, glycerol, triethanolamine, or metaxylenediamine are preferable.

[0073] In addition, when a composition containing a polyester polyol having residual carboxylic acid groups, such as polyester polyol (A1'), is used as the polyol composition (X), the polyisocyanate composition (Y) may contain an epoxy compound. Examples of the epoxy compound include diglycidyl ether of bisphenol A and its oligomer, diglycidyl ether of hydrogenated bisphenol A and its oligomer, orthophthalic acid diglycidyl ester, isophthalic acid diglycidyl ester, terephthalic acid diglycidyl ester, p-oxybenzoic acid diglycidyl ester, tetrahydrophthalic acid diglycidyl ester, hexahydrophthalic acid diglycidyl ester, succinic acid diglycidyl ester, adipic acid diglycidyl ester, sebacic acid diglycidyl ester, ethylene glycol diglycidyl ether, and propylene glycol diglycidyl. ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polyalkylene glycol diglycidyl ethers, trimellitic acid triglycidyl ester, triglycidyl isocyanurate, 1,4-diglycidyloxybenzene, diglycidyl propylene urea, glycerol triglycidyl ether, trimethylolethane triglycidyl ether, trimethylolpropane triglycidyl ether, pentaerythritol tetraglycidyl ether, triglycidyl ether of glycerol alkylene oxide adduct, and the like.

[0074] When an epoxy compound is used, a commonly known epoxy curing accelerator may be appropriately added for the purpose of accelerating curing within a range that does not impair the object of the present invention.

[0075] When a composition containing a polyol having a polymerizable carbon-carbon double bond such as polyester polyol (A3) is used as the polyol composition (X), a known polymerization catalyst can be used in combination to promote the polymerization of the carbon-carbon double bond, and one example is a transition metal complex. The transition metal complex is not particularly limited as long as it is a compound capable of oxidatively polymerizing the polymerizable double bond. For example, salts of metals such as cobalt, manganese, lead, calcium, cerium, zirconium, zinc, iron, and copper with octylic acid, naphthenic acid, neodecanoic acid, stearic acid, resin acid, tall oil fatty acid, tung oil fatty acid, linseed oil fatty acid, soybean oil fatty acid, and the like can be used. The amount of the transition metal complex to be blended is preferably 0 to 10 parts by mass, more preferably 0 to 3 parts by mass, based on the resin solid content contained in the polyol composition (X).

[0076] The polyol composition (X) and the polyisocyanate composition (Y) are preferably mixed so that the equivalent ratio of the hydroxyl group contained in the polyol composition (X) to the isocyanate group contained in the polyisocyanate composition (Y) is 1 / 0.5 to 1 / 10, and more preferably 1 / 1 to 1 / 5. If the isocyanate compound is excessive, the excess isocyanate compound remaining in the cured coating film of the adhesive may bleed out from the adhesive layer. On the other hand, if the reactive functional group contained in the polyisocyanate composition (Y) is insufficient, the adhesive strength may be insufficient.

[0077] The gas barrier adhesive may contain various additives within limits that do not impair the adhesiveness and gas barrier properties.

[0078] As such an additive, an inorganic filler may be used. Examples of the inorganic filler include silica, alumina, aluminum flakes, glass flakes, etc. In particular, it is preferable to use a plate-like inorganic compound as the inorganic filler, since it improves the adhesive strength, gas barrier properties, light shielding properties, etc. Examples of the plate-like inorganic compounds include hydrated silicates (phyllosilicate minerals, etc.), kaolinite-serpentine clay minerals (halloysite, kaolinite, endelite, dickite, nacrite, etc., antigorite, chrysotile, etc.), pyrophyllite-talc (pyrophyllite, talc, keroli, etc.), smectite clay minerals (montmorillonite, beidellite, nontronite, saponite, hectorite, sauconite, stevensite, etc.), vermiculite clay minerals (vermiculite, etc.), mica or mica clay minerals (muscovite, phlogopite, etc., mica, margarite, tetrasilylic mica, taeniolite, etc.), chlorite (cookite, sudoite, clinochlore, chamosite, nimite, etc.), hydrotalcite, plate-like barium sulfate, boehmite, aluminum polyphosphate, etc. These minerals may be natural clay minerals or synthetic clay minerals. The plate-like inorganic compounds can be used alone or in combination of two or more.

[0079] The plate-like inorganic compound may be ionic, having an electric charge between layers, or nonionic, having no electric charge. The presence or absence of an electric charge between layers does not directly affect the gas barrier properties of the adhesive layer. However, ionic plate-like inorganic compounds and inorganic compounds having swelling properties in water are poorly dispersible in solvent-based adhesives, and increasing the amount of the compound may cause the adhesive to thicken or become thixotropic, resulting in a decrease in applicability. For this reason, it is preferable that the plate-like inorganic compound is nonionic, having no electric charge between layers.

[0080] The average particle size of the plate-like inorganic compound is not particularly limited, but is preferably 0.1 μm or more, and more preferably 1 μm or more, for example. If it is smaller than 0.1 μm, the detour path of oxygen molecules is not long, and sufficient improvement in gas barrier properties cannot be expected. The upper limit of the average particle size is not particularly limited, but if the particle size is too large, defects such as streaks may occur on the coated surface depending on the coating method. For this reason, as an example, the average particle size is preferably 100 μm or less, and more preferably 20 μm or less. In this specification, the average particle size of the plate-like inorganic compound refers to the particle size that appears most frequently when the particle size distribution of the plate-like inorganic compound is measured using a light scattering measuring device.

[0081] The aspect ratio of the plate-like inorganic compound is preferably high in order to improve the gas barrier property by the labyrinth effect of oxygen. Specifically, the aspect ratio is preferably 3 or more, more preferably 10 or more, and most preferably 40 or more.

[0082] The amount of the plate-like inorganic compound is arbitrary. As an example, the amount of the plate-like inorganic compound is 5 to 50 parts by mass when the total mass of the solid contents of the polyol composition (X), the polyisocyanate composition (Y), and the plate-like inorganic compound is 100 parts by mass.

[0083] The gas barrier adhesive may contain an adhesion promoter. Examples of the adhesion promoter include silane coupling agents such as hydrolyzable alkoxysilane compounds, titanate coupling agents, aluminum coupling agents, epoxy resins, etc. Silane coupling agents and titanate coupling agents are expected to have the effect of improving adhesion to various film materials.

[0084] When the gas barrier adhesive layer needs to be acid-resistant, the gas barrier adhesive may contain a known acid anhydride. Examples of the acid anhydride include phthalic anhydride, succinic anhydride, HET anhydride, hymic anhydride, maleic anhydride, tetrahydrophthalic anhydride, hexahydraphthalic anhydride, tetrabromophthalic anhydride, tetrachlorophthalic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenotetracarboxylic anhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 5-(2,5-oxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, and styrene-maleic anhydride copolymer.

[0085] If necessary, a compound having an oxygen scavenging function may be further added. Examples of the compound having an oxygen scavenging function include low molecular weight organic compounds that react with oxygen, such as hindered phenols, vitamin C, vitamin E, organic phosphorus compounds, gallic acid, and pyrogallol, and transition metal compounds, such as cobalt, manganese, nickel, iron, and copper.

[0086] The gas barrier adhesive may contain a compound represented by the following general formula (1) or (2).

[0087] [ka] (In general formula (1), R1 to R3 are groups selected from a hydrogen atom, an alkyl group having 1 to 30 carbon atoms, a (meth)acryloyl group, a phenyl group which may have a substituent, and an alkyl group having 1 to 4 carbon atoms which has a (meth)acryloyloxy group, at least one of which is a hydrogen atom, and n is an integer of 1 to 4.)

[0088] [ka] (In the general formula (2), R4 and R5 each represent a group selected from a hydrogen atom, an alkyl group having 1 to 30 carbon atoms, a (meth)acryloyl group, a phenyl group which may have a substituent, and an alkyl group having 1 to 4 carbon atoms and having a (meth)acryloyloxy group; m and l each represent an integer of 1 to 4, p represents an integer of 0 to 30, and q represents an integer of 0 to 30, except for the case where both p and q are 0.)

[0089] Specific examples of the compounds represented by the above general formulas (1) and (2) include phosphoric acid, pyrophosphoric acid, triphosphoric acid, methyl acid phosphate, ethyl acid phosphate, butyl acid phosphate, dibutyl phosphate, 2-ethylhexyl acid phosphate, bis(2-ethylhexyl) phosphate, isododecyl acid phosphate, butoxyethyl acid phosphate, oleyl acid phosphate, tetracosyl acid phosphate, 2-hydroxyethyl methacrylate acid phosphate, polyoxyethylene alkyl ether phosphate, and the like.

[0090] The compound represented by the above general formula (1) or (2) is preferably blended in an amount of 0.005 to 10 mass %, more preferably 0.01 to 1 mass %, based on the total solid content of the gas barrier adhesive.

[0091] In order to improve adhesion to various film materials immediately after application, a tackifier such as a xylene resin, a terpene resin, a phenol resin, a rosin resin, etc. may be added as necessary. When these are added, the amount of the tackifier is preferably in the range of 0.01 to 5 parts by mass per 100 parts by mass of the total solid content of the polyol composition (X) and the polyisocyanate composition (Y).

[0092] When the polyol composition (X) contains the polyester polyol (A2), active energy rays can be used as a method for reacting the polymerizable carbon-carbon double bonds. Known techniques can be used for the active energy rays, and the composition can be cured by irradiating with ionizing radiation such as electron beams, ultraviolet rays, or gamma rays. When curing with ultraviolet rays, a known ultraviolet ray irradiation device equipped with a high-pressure mercury lamp, an excimer lamp, a metal halide lamp, or the like can be used.

[0093] When curing is performed by irradiation with ultraviolet rays, it is preferable to add about 0.1 to 20 parts by mass of a photo (polymerization) initiator that generates radicals upon irradiation with ultraviolet rays, based on 100 parts by mass of the polyester polyol (A2), as necessary.

[0094] Examples of radical-generating photo(polymerization) initiators include hydrogen abstraction types such as benzil, benzophenone, Michler's ketone, 2-chlorothioxanthone, and 2,4-diethylthioxanthone, and photocleavage types such as benzoin ethyl ether, diethoxyacetophenone, benzil methyl ketal, hydroxycyclohexyl phenyl ketone, and 2-hydroxy-2-methyl phenyl ketone. These can be used alone or in combination.

[0095] In addition, the gas barrier adhesive may contain a stabilizer (antioxidant, heat stabilizer, ultraviolet absorber, etc.), a plasticizer, an antistatic agent, a lubricant, an antiblocking agent, a colorant, a crystal nucleating agent, etc. These various additives may be added in advance to either or both of the polyol composition (X) and the polyisocyanate composition (Y), or may be added when the polyol composition (X) and the polyisocyanate composition (Y) are mixed.

[0096] The gas barrier adhesive used in the present invention may be in the form of either a solvent-based or solventless type. In this specification, the solvent-based adhesive refers to a form used in a method in which the adhesive is applied to a substrate, heated in an oven or the like to volatilize the organic solvent in the coating film, and then laminated to another substrate, that is, a so-called dry lamination method. Examples of the solvent used include toluene, xylene, methylene chloride, tetrahydrofuran, methyl acetate, ethyl acetate, n-propyl acetate, n-butyl acetate, acetone, methyl ethyl ketone (MEK), cyclohexanone, toluene, xylol, n-hexane, cyclohexane, and the like. Either or both of the polyol composition (X) and the polyisocyanate composition (Y) contain the above-mentioned organic solvent. In the case of a solvent-based adhesive, the solvent used as a reaction medium during the production of the constituent components of the polyol composition (X) or the polyisocyanate composition (Y) may also be used as a diluent during coating.

[0097] A solvent-free adhesive refers to a form used in a method in which an adhesive is applied to a substrate and then laminated to another substrate without a process of volatilizing the solvent by heating in an oven or the like, that is, a so-called non-solvent lamination method. Neither the polyol composition (X) nor the polyisocyanate composition (Y) substantially contains the above-mentioned organic solvent. When the organic solvent used as a reaction medium in the manufacture of the components of the polyol composition (X) or the polyisocyanate composition (Y) or the raw materials thereof cannot be completely removed and a trace amount of organic solvent remains in the polyol composition (X) or the polyisocyanate composition (Y), it is understood that the polyol composition (X) does not substantially contain an organic solvent. In addition, when the polyol composition (X) contains a low molecular weight alcohol, the low molecular weight alcohol reacts with the polyisocyanate composition (Y) to become a part of the coating film, so there is no need to volatilize it after coating. Therefore, such a form is also treated as a solvent-free adhesive.

[0098] When the gas barrier adhesive is a solvent-based adhesive, the gas barrier adhesive is applied to one of the first and second substrates using a roll such as a gravure roll, and the organic solvent is evaporated by heating in an oven or the like, and then the other substrate is laminated to obtain the laminate of the present invention. It is preferable to perform an aging treatment after lamination. The aging temperature is preferably room temperature to 80°C, and the aging time is preferably 12 to 240 hours.

[0099] When the gas barrier adhesive is a solventless type, the gas barrier adhesive, which has been preheated to about 40°C to 100°C, is applied to one of the first and second substrates using a roll such as a gravure roll, and the other is immediately bonded to obtain the laminate of the present invention. It is preferable to carry out an aging treatment after lamination. The aging temperature is preferably room temperature to 70°C, and the aging time is preferably 6 to 240 hours.

[0100] The amount of gas barrier adhesive to be applied is adjusted as appropriate. For example, in the case of a solvent-based adhesive, the solid content is 1 g / m 2 More than 10g / m 2 Less than 1 g / m 2 More than 5g / m 2 Adjust the amount of adhesive applied as follows: For solvent-free adhesive, the amount of adhesive applied is, for example, 1 g / m 2 More than 10g / m 2 Less than 1 g / m 2 More than 5g / m 2 The following is the result.

[0101] (Printing layer) The laminate of the present invention may be provided with a printed layer. The printed layer is a layer on which characters, figures, symbols, other desired patterns, etc. are printed using a printing ink between the first substrate and the gas barrier adhesive layer, or on the surface of the first substrate opposite to the gas barrier adhesive layer. When a barrier layer is provided on the first substrate, the printed layer is provided directly on the barrier layer or via another layer. That is, the printed layer is disposed between the barrier layer and the gas barrier adhesive layer. When a barrier layer is not provided on the first substrate, the printed layer may be provided directly on the first substrate, or may be provided via, for example, a primer layer for improving adhesion between the first substrate and the printed layer.

[0102] Alternatively, from the viewpoint of improving recyclability, the printed layer may be provided via a deinking primer to make it easier to remove the printed layer in the manufacturing method for recycled plastic described below. When the laminate or packaging material of the present invention is used for the production of recycled plastics without removing the printed layer, it is preferable that the area of ​​the printed layer is as small as possible in order to suppress discoloration of the recycled plastics. The proportion of the portion of the laminate where the printed layer is provided per unit area is preferably 50% or less, more preferably 30% or less, and even more preferably 10% or less.

[0103] The printing method and printing ink are not particularly limited, and known printing methods and printing inks can be used. Printing inks using gravure printing, flexographic printing, lithographic offset printing, inkjet recording printing, etc. are often used for the film used as the substrate. Printing inks that combine these printing methods with a method of curing with active energy rays such as ultraviolet rays (UV), LEDs, and electron beams (EB), or a method of curing with heat, etc., are also used. Depending on the solvent used, the inks may be referred to as water-based inks or organic solvent-based inks.

[0104] Specific examples include gravure printing ink, flexographic printing ink (in some industries, gravure printing ink and flexographic printing ink are called liquid ink), ultraviolet-curable ink for lithographic offset printing, electron beam-curable ink for lithographic offset printing, ultraviolet-curable ink for inkjet recording and printing, electron beam-curable ink for inkjet recording and printing, etc. Biomass inks using biomass raw materials are also used as appropriate.

[0105] The printing ink may contain a resin, a colorant, and a solvent as essential components, or may be a so-called clear ink that contains a resin and a solvent but does not substantially contain a colorant. The printing layer may be provided on the entire surface of the first substrate, or may be provided only on a part of the first substrate.

[0106] Taking the case where the printing ink is a gravure printing ink or a flexographic printing ink as an example, the resin used in the printing ink is not particularly limited, and examples thereof include acrylic resin, polyester resin, styrene resin, styrene-maleic acid resin, maleic acid resin, polyamide resin, polyurethane resin, vinyl chloride-vinyl acetate copolymer resin, vinyl chloride-acrylic copolymer resin, ethylene-vinyl acetate copolymer resin, vinyl acetate resin, polyvinyl chloride resin, chlorinated polypropylene resin, cellulose-based resin, epoxy resin, alkyd resin, rosin-based resin, rosin-modified maleic acid resin, ketone resin, cyclized rubber, chlorinated rubber, butyral, petroleum resin, etc., and one or more of them can be used in combination. Preferably, at least one or two or more selected from polyurethane resin, vinyl chloride-vinyl acetate copolymer resin, and cellulose-based resin are used.

[0107] Colorants used in printing inks include inorganic pigments such as titanium oxide, red iron oxide, antimony red, cadmium red, cadmium yellow, cobalt blue, Prussian blue, ultramarine, carbon black, and graphite; organic pigments such as soluble azo pigments, insoluble azo pigments, azo lake pigments, condensed azo pigments, copper phthalocyanine pigments, and condensed polycyclic pigments; and extender pigments such as calcium carbonate, kaolin clay, barium sulfate, aluminum hydroxide, and talc.

[0108] The organic solvent used in the printing ink preferably does not contain an aromatic hydrocarbon-based organic solvent. More specifically, examples of the organic solvent include alcohol-based organic solvents such as methanol, ethanol, n-propanol, isopropanol, and butanol, ketone-based organic solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, ester-based organic solvents such as methyl acetate, ethyl acetate, propyl acetate, and butyl acetate, aliphatic hydrocarbon-based organic solvents such as n-hexane, n-heptane, and n-octane, and alicyclic hydrocarbon-based organic solvents such as cyclohexane, methylcyclohexane, ethylcyclohexane, cycloheptane, and cyclooctane, and these can be used alone or in combination of two or more.

[0109] In consideration of the establishment of a recycling-based society that should develop in a sustainable manner (sustainability), it is also preferable to use a gravure printing ink or flexographic printing ink that uses raw materials derived from plants as the liquid printing ink used in the present invention.

[0110] Examples of plant-derived raw materials include cellulose resins such as cellulose acetate propionate resin and nitrocellulose; polyamide resins using dimer acids or polymerized fatty acids derived from natural oils such as soybean oil, palm oil, and rice bran oil; polycarboxylic acids such as succinic acid, succinic anhydride, adipic acid, azelaic acid, sebacic acid, dimer acid, glutaric acid, and malic acid; polyols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, pentylene glycol, 1,10-dodecanediol, dimer diol, and isosorbide; and polyisocyanates such as 1,5-pentamethylene diisocyanate and dimer diisocyanate. These polycarboxylic acids include succinic acid, succinic anhydride, adipic acid, azelaic acid, sebacic acid, dimer acid, glutaric acid, and malic acid. The polyols include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, pentylene glycol, 1,10-dodecanediol, dimer diol, and isosorbide. The polyisocyanates include 1,5-pentamethylene diisocyanate and dimer diisocyanate. These polyisocyanates include biomass polyurethanes and rosin resins.

[0111] As the biomass gravure printing ink or flexographic printing ink, commercially available products listed in the Japan Organics Resources Association can also be used.

[0112] (Structure of Laminate) Examples of the configuration of the laminate of the present invention include: (1) First substrate / gas barrier adhesive layer / second substrate (2) First substrate / printed layer / gas barrier adhesive layer / second substrate (3) Printing layer / first substrate / gas barrier adhesive layer / second substrate In the above configuration example, either or both of the first substrate and the second substrate have a barrier layer, as described above.

[0113] The laminate of the present invention may further include another substrate. Examples of the structure of such a laminate include: (4) First substrate / adhesive layer / third substrate / adhesive layer / second substrate (5) First substrate / printing layer / adhesive layer / third substrate / adhesive layer / second substrate (6) Printing layer / first substrate / adhesive layer / third substrate / adhesive layer / second substrate In the configuration examples (4) to (6), one or both of the two adhesive layers are the gas barrier adhesive layer described above. When only one of the two adhesive layers is a gas barrier adhesive layer, the other adhesive layer can be formed of any adhesive. Examples of such adhesives include one-liquid or two-liquid urethane adhesives. As the third substrate, a substrate similar to the first substrate containing the same resin type as the first substrate can be used.

[0114] In the above configuration examples (4) to (6), it is preferable that the first substrate is either an OPP film or an OPE film which may have a barrier layer, the second substrate is either a CPP film or an LLDPE film which may have a barrier layer, and the third substrate is either an OPP film or an OPE film.

[0115] In addition, from the viewpoint of recyclability, the laminate of the present invention preferably does not include a metal foil layer. Since the laminate of the present invention has excellent gas barrier properties even without these layers, the first substrate and / or the second substrate may or may not include an inorganic vapor deposition layer such as silica or alumina, or a metal vapor deposition layer such as aluminum, which is generally used to impart gas barrier properties to the laminate.

[0116] <Packaging material> The laminate of the present invention can be used as a multi-layer packaging material for protecting foods, medicines, etc. When used as a multi-layer packaging material, the layer structure can be changed depending on the contents, the environment of use, and the form of use.

[0117] The packaging material of the present invention can be obtained, for example, by overlapping the heat seal layers of the laminate of the present invention so that they face each other, and then heat sealing the peripheral edge. Examples of the bag-making method include folding or overlapping the laminate of the present invention so that the surfaces of the inner layers (the surfaces of the sealant film) face each other, and heat sealing the peripheral edge, for example, by a side seal type, a two-sided seal type, a three-sided seal type, a four-sided seal type, an envelope seal type, a grooving seal type, a pleated seal type, a flat bottom seal type, a square bottom seal type, a gusset type, or other heat seal type. The packaging material of the present invention can take various forms depending on the contents, the environment of use, and the form of use. Self-supporting packaging materials (standing pouches) are also possible. Heat sealing can be performed by known methods such as bar seal, rotary roll seal, belt seal, impulse seal, high frequency seal, and ultrasonic seal.

[0118] The packaging material of the present invention is filled with contents through its opening, and the opening is then heat-sealed to produce a product using the packaging material of the present invention. The contents to be filled include confectioneries such as rice crackers, bean snacks, nuts, biscuits and cookies, wafer snacks, marshmallows, pies, semi-dried cakes, candies, and snacks, staple foods such as bread, snack noodles, instant noodles, dried noodles, pasta, aseptically packaged cooked rice, porridge, porridge, packaged rice cakes, and cereal foods, pickles, boiled beans, natto, miso, frozen tofu, tofu, nametake mushrooms, konjac, wild vegetable processed products, jams, peanut cream, salads, frozen vegetables, and processed potato products, livestock processed products such as hams, bacon, sausages, processed chicken products, and corned beef, and fish ham and sausages. Examples of the food products that can be used include processed fishery products such as fish paste, fish paste products, kamaboko, nori, tsukudani, bonito flakes, shiokara, smoked salmon, and spicy cod roe, fruit pulp such as peaches, mandarin oranges, pineapples, apples, pears, and cherries, vegetables such as corn, asparagus, mushrooms, onions, carrots, radishes, and potatoes, prepared foods such as frozen and chilled prepared foods, typified by hamburger steaks, meatballs, seafood fries, gyoza dumplings, and croquettes, dairy products such as butter, margarine, cheese, cream, instant creamy powder, and infant formula, liquid seasonings, retort curry, and pet food. The packaging material of the present invention can also be used as a packaging material for cigarettes, medicines such as disposable hand warmers and infusion packs, cosmetics, and vacuum insulation materials.

[0119] Alternatively, the packaging material of the present invention may be a lid material using the laminate of the present invention.

[0120] <Recycled plastics> The laminate and packaging material of the present invention have excellent recyclability and can be used as a raw material for recycled plastics. The recycled plastics of the present invention are regenerated using the laminate and packaging material of the present invention as raw materials. The method for recycling the laminate and packaging material is not particularly limited, and known methods can be used. Examples include a method in which the laminate and packaging material are crushed, melt-kneaded, and then pelletized and molded, and a method in which the crushed laminate and packaging material are directly fed into a molding machine without going through melt-kneading and pelletization, and melt-kneaded in the heating cylinder of the molding machine to obtain a molding raw material.

[0121] The laminate and packaging material can be crushed using a known crusher. The crusher is not particularly limited, and examples thereof include a method using a jaw crusher, an impact crusher, a cutter mill, a stamp mill, a ring mill, a roller mill, a jet mill, or a hammer mill. The size of the pieces of the printed matter or laminate (A) is preferably 1 mm to 40 mm in side length, more preferably 8 mm to 20 mm.

[0122] The crushed laminate and packaging material are preferably washed before being subjected to heat melting. The washing method may be a batch type or a continuous type, and water, a detergent, a neutralizing agent, or an alkaline aqueous solution may be used. The washed laminate and packaging material are preferably dehydrated and dried. The dehydration method is preferably a centrifugal dehydration method, and the drying method is preferably a hot air drying method.

[0123] The crushed laminate and packaging material are heated and melted at 120 to 280°C, and further kneaded. The temperature at which the laminate and packaging material are melted can be adjusted taking into consideration the glass transition temperature or melting temperature of the laminate or packaging material, the shape at the time of pelletization, and the pressure applied in the molding process. The screw rotation speed during kneading is, for example, 50 to 1000 RPM.

[0124] The laminate and packaging material thus melt-kneaded are cooled and chopped into pellets. Examples of the pelletizing method include hot cut method and strand cut method, but are not particularly limited. In order to prevent foreign matter from being mixed into the pellets, it is preferable that a screen mesh is provided at the discharge part of the melt-kneaded laminate and packaging material. Examples of the screen mesh include plain weave, twill weave, plain tatami weave, and twill tatami weave, and punching metal type. Considering the pressure of the discharge part and clogging, the size of the screen mesh is preferably 40 mesh or more, more preferably 80 mesh or more, and even more preferably 120 mesh or more. Examples of the cooling method include air cooling, wind cooling, and water cooling. In the present invention, it is preferable to include a water cooling step. It is preferable to cool to 20°C to 80°C, and more preferably to cool to 30°C to 60°C.

[0125] The laminate of the present invention can be used for the production of recycled plastics as described above since the first substrate and the second substrate are made of the same resin type and have excellent recyclability. However, the laminate may be used for the production of recycled plastics after peeling the first substrate from the second substrate by immersing the laminate in an alkaline solution such as an aqueous sodium hydroxide solution for a certain period of time. The laminate may also be used for the production of recycled plastics after removing the printed layer. The printed layer can be removed by a known method. When the barrier layer is provided on the surface of the first substrate and / or the second substrate and contains polyvinyl alcohol, the barrier layer is more preferable because it has excellent recyclability and also serves as a release layer that facilitates peeling of the first substrate from the second substrate or separation of the adhesive layer, the ink layer, and the coating layer.

[0126] The recycled plastic of the present invention may contain known additives, such as at least one antioxidant selected from the group consisting of phenols and phosphorus-based additives, at least one lubricant selected from the group consisting of fatty acid amides, alkylene fatty acid amides, metal soaps, and esters, a hindered amine weathering stabilizer, a wax having an acid value of 5 mgKOH / g or less, and at least one antistatic agent selected from the group consisting of fatty acid sulfonates and fatty acid esters.

[0127] The recycled plastic of the present invention may contain virgin plastic as a raw material in addition to the laminate and packaging material of the present invention. The virgin plastic to be added is of the same resin type as that of the first substrate and the second substrate. The virgin plastic may be added when the laminate and packaging material of the present invention are pelletized, or when the pelletized recycled plastic of the present invention is molded. The virgin plastic may be added both when pelletizing and when molding the recycled plastic. The amount of virgin plastic used in combination when pelletizing the laminate and packaging material of the present invention is, for example, in the range of 100:0 to 25:75 (mass ratio) of laminate and packaging material:virgin plastic. The amount of virgin plastic used when molding the pelletized recycled plastic of the present invention is, for example, in the range of 100:0 to 25:75 (mass ratio) of recycled plastic:virgin plastic.

[0128] The recycled plastic of the present invention can be used as a raw material for various plastic products. Examples of plastic products include, but are not limited to, containers such as pallets and containers for transportation, bottles, hangers, stationery, pots and cups, disposable cutlery, and playground equipment. The recycled plastic can be recycled as a film, and the recycled film can be molded and used as, for example, a cushioning material for transporting fruit, but is not limited to this.

Claims

1. A first substrate; A second substrate containing the same resin type as the first substrate and having heat sealability; a gas barrier adhesive layer disposed between the first substrate and the second substrate, At least one of the first substrate and the second substrate comprises a barrier layer that contains a water-based non-halogen-containing resin and has a thickness of 0.1 μm or more and 1 μm or less.

2. 2. The laminate according to claim 1, wherein the barrier layer comprises at least one selected from the group consisting of polyvinyl alcohol, ethylene-vinyl alcohol copolymer, polycarboxylic acid, and polyethyleneimine.

3. The laminate according to claim 1 , wherein the barrier layer comprises an inorganic compound.

4. The laminate according to claim 1 , wherein the first substrate and the second substrate each contain an olefin-based resin.

5. A packaging material comprising the laminate according to any one of claims 1 to 4.

6. A recycled plastic obtained by using the laminate according to any one of claims 1 to 4 as a raw material.

Citation Information

Patent Citations

  • Low-elution packaging material

    JP2004238050A

  • Laminate and method for manufacturing laminate

    JP2014004799A